2016
DOI: 10.21315/km2016.34.2.1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Perceived Social Support and Self-Efficacy on Resilience among First Year Malaysian Students

Abstract: To cite this article: Shreas Suresh Narayanan and Alexius Cheang Weng Onn. 2016. The influence of perceived social support and self-efficacy on resilience among first year Malaysian students. Kajian Malaysia 34 (2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 49 publications
2
18
0
7
Order By: Relevance
“…Family is the main support system for the elderly in maintaining their health. This is in line with the results of a study stating that social support can come from family and close friends (Narayanan & Onn, 2016). The role of family in elderly care includes maintaining or caring for the elderly, maintaining and improving mental status, anticipating socioeconomic changes, and providing motivation as well as facilitating spiritual needs for the elderly.…”
Section: Disscusion Social Supportssupporting
confidence: 85%
“…Family is the main support system for the elderly in maintaining their health. This is in line with the results of a study stating that social support can come from family and close friends (Narayanan & Onn, 2016). The role of family in elderly care includes maintaining or caring for the elderly, maintaining and improving mental status, anticipating socioeconomic changes, and providing motivation as well as facilitating spiritual needs for the elderly.…”
Section: Disscusion Social Supportssupporting
confidence: 85%
“…Adapun yang termasuk significant others yaitu kelompok sosial, yang dalam hal ini termasuk teman-teman sejawat (Zimet, 1988, Wang et al, .2017. Hal ini sejalan dengan Narayanan & Onn (2016) dan Wang et al (2017) yang menyatakan dukungan sosial bisa berasal dari keluarga, teman dan teman sekerja.…”
Section: Pendahuluanunclassified
“…Dukungan secara emosional membuat seseorang merasakan adanya perhatian yang membuat mereka merasa lebih nyaman saat menghadapi kesulitan (Xu and Burleson, 2001). Melalui adanya hubungan yang berarti serta dukungan sosial sangat penting yang menandakan seseorang diterima (Tusaie and Dyer, 2004), ada perasaan memiliki (Sippel et al, 2015) serta menurunkan stress (Ren, 2018) dan emosi negatif yang pada akhirnya meningkatkan resiliensi (Narayanan and Onn, 2016).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Bulathwatta et al (2017) have found that those who participated in the study in resilience and durability used different levels of resistance and emotional intelligence. Narayanan and Onn (2016) have found that social support and self-efficacy affect psychological resilience.…”
Section: Psychological Resiliencementioning
confidence: 99%